2019
DOI: 10.3390/molecules24193613
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Cosmeceutical Potential of Common Barbery (Berberis vulgaris L.) Root Bark Extracts Obtained by Optimization of ‘Green’ Ultrasound-Assisted Extraction

Abstract: Berberis vulgaris is rich in berberine, an isoquinoline alkaloid, with antidiabetic activity, often used topically for skin-related problems. The aim of this work was to develop a “green” method for berberine extraction using mixtures of water with glycerol, a non-toxic, environmentally-friendly solvent. Response surface methodology based on Box–Behnken design was used to optimize the experimental conditions for ultrasound-assisted extraction of berberine and anti-radical components from B. vulgaris root bark.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…An efficient UAE process should maximize the recovery of target compounds with minimal degradation, resulting in an extract with high biological activity. Ideally, this should be accomplished using "green" environmentally friendly technologies and low-cost raw materials and solvents [10]. However, in order to determine the best UAE conditions for extraction of bioactive constituents, it is often necessary to perform multiple experiments and evaluate not only the direct influence of extraction variables, but their interactions as well.…”
Section: Effect Of Uae Variables On Phenolic Acid Extraction Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…An efficient UAE process should maximize the recovery of target compounds with minimal degradation, resulting in an extract with high biological activity. Ideally, this should be accomplished using "green" environmentally friendly technologies and low-cost raw materials and solvents [10]. However, in order to determine the best UAE conditions for extraction of bioactive constituents, it is often necessary to perform multiple experiments and evaluate not only the direct influence of extraction variables, but their interactions as well.…”
Section: Effect Of Uae Variables On Phenolic Acid Extraction Yieldmentioning
confidence: 99%
“…High temperature and ultrasound power levels may improve the extraction process by reducing the viscosity of the solvent and by increasing the kinetic energy of the molecules in the solution. However, they may also lead to degradation of sensitive phytochemicals, including phenolic compounds [10]. Similarly, long extraction times may increase the amount of the extracted target compounds.…”
Section: Effect Of Uae Variables On Phenolic Acid Extraction Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Berberine, a benzylisoquinoline alkaloid is one of the main components of Berberis species and has been reported for many pharmacological activities through enhancing the protection of cells against oxidative stress, immune system, heart, liver and kidney function (Neag et al ., 2018). Although the main component of most Berberis species and specifically barberry has reported to be berberine, yet experimental studies have shown that the antioxidant activity of barberry is not solely correlated with the berberine content (Dulić et al ., 2019), which suggests that barberry also contains other bioactive compounds with functional properties. A wide range of phenolic compounds, organic acids and anthocyanins have been identified in different Berberis species (Berenji Ardestani et al ., 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of these herbs with antioxidant properties is Berberis vulgaris L, a shrub of the genus Berberis, which is mainly cultivated in the region of South Khorasan in Iran and is one of the few plants whose root, peel, stem, leaves, flower, and fruits are used for various nutritive and medicinal purposes (Taheri et al, 2012). This plant is cultivated in many regions of the world and has a long history of use in traditional medicine (Dulić et al, 2019;Tabeshpour et al, 2017). Some of the alkaloids in black barberry when chemically analysed include berberine, palmatine, oxyaconthine, and berbamine, having each medicinal benefit.…”
Section: Introductionmentioning
confidence: 99%